MALE AND FEMALE OBESITY AND ITS IMPACT ON FERTILITY: A SYSTEMATIC REVIEW OF THE RELATIONSHIP AND OUTCOMES (CAHIERS MAGELLANES-NS, 2024)
The current paper focuses on obesity, a global concern to health that brings far-reaching implications, including high-impact effects on the state of reproductive health. Therefore, this systematic review aims to synthesize current evidence on the relationship between obesity and fertility in males and females and its effects on conception, pregnancy, and offspring health outcomes. A detailed literature search across various literature databases produced 12 good-quality studies published from 2010 through 2024. Consequently, this review showed that obesity had a bad effect on male fertility through changes in sperm parameters and hormonal imbalance, probably due to epigenetic alterations. In females, it has been linked to ovulatory dysfunction, impaired quality of the oocyte, and altered endometrial receptivity. Male and female obesity have been linked to poor success rates of assisted reproductive technologies. This review commented on the potential transgenerational effects of parental obesity on offspring health mediated by epigenetic mechanisms. Indeed, the findings emphasized that strategies on reproductive health must therefore embody tackling obesity, including care of people planning a pregnancy and fertility treatments. Future research directions should aim at clarifying the molecular mechanisms, developing targeted interventions, and assessment of offspring health outcomes in long-term follow-up studies